Orbital Angular Momentum Multiplexing and Demultiplexing by a Single Metasurface. Issue 2 (2nd November 2016) - Li, Yang; Li, Xiong; Chen, Lianwei; Pu, Mingbo; Jin, Jinjin; Hong, Minghui; Luo, Xiangang
Abstract : Orbital angular momentum (OAM) has recently gained much interest in high‐speed optical communication due to its spatial orthogonality. However, complex spatial phase distributions of OAM make the components difficult for nano‐photonic integration. In this work, a method to multiplex and demultiplex multiple OAMs, wavelengths, and polarizations channels by a highly integrated off‐axis technique on a metasurface is presented. As a multiplexer, beams without OAM can be transferred into coaxial beams carrying different OAM features by different incident angles; as a demultiplexer, coaxial beams carrying multi‐OAMs can be divided into different directions with fundamental modes. Furthermore, the component based on dipole optical antenna metasurface can be used not only as an OAM multiplexer/demultiplexer but also as a multiplexer/demultiplexer to achieve wavelength division multiplexing and polarization‐division multiplexing, as both these applications are based on the conservations of momentum and angular momentum. For practical applications, phase‐only hologram is analyzed to demonstrate multiple functions of this method. Abstract : A method is presented to multiplex and demultiplex multiple orbital angular momentums, wavelengths, and polarization channels by a highly integrated off‐axis technique on a single metasurface for high‐speed optical communication. It opens an area of integration and simplification on optical systems for simultaneously manipulating spatial distribution, wavelength, and polarization.